2021
DOI: 10.3390/antibiotics10111337
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bred ε2-Phages Have an Improved Host Range and Virulence against Uropathogenic Escherichia coli over Their Ancestor Phages

Abstract: Alternative treatments for Escherichia coli infections are urgently needed, and phage therapy is a promising option where antibiotics fail, especially for urinary tract infections (UTI). We used wastewater-isolated phages to test their lytic activity against a panel of 47 E. coli strains reflecting the diversity of strains found in UTI, including sequence type 131, 73 and 69. The plaquing host range (PHR) was between 13 and 63%. In contrast, the kinetic host range (KHR), describing the percentage of strains fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…To improve the activity of phages in plasma, a combination of phages was subjected to directed evolution (what we called breeding), by passaging them with 24 different S. aureus strains and in presence of plasma for 20 rounds as described previously 9 , 28 . The single phages isolated after breeding did not show an improved activity in plasma in comparison to the ancestor phages (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…To improve the activity of phages in plasma, a combination of phages was subjected to directed evolution (what we called breeding), by passaging them with 24 different S. aureus strains and in presence of plasma for 20 rounds as described previously 9 , 28 . The single phages isolated after breeding did not show an improved activity in plasma in comparison to the ancestor phages (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In phage research, homologous recombination between related phages was used in one of the earliest methods to modify phage genomes, known as phage crosses [18]. Co-infection of host bacteria with two phages showing different phenotypic characteristics results in recombination between the two parental phage genomes and subsequent release of progeny phages with new combinations of the parental phenotypes (Figure 1A) [19][20][21]. Phage crosses have been commonly used to exchange and combine phage genes involved in receptor recognition, resulting in altered host range, or to study the interaction between phages and newly identified bacterial defense systems [19,[21][22][23].…”
Section: Homologous Recombinationmentioning
confidence: 99%
“…Co-infection of host bacteria with two phages showing different phenotypic characteristics results in recombination between the two parental phage genomes and subsequent release of progeny phages with new combinations of the parental phenotypes (Figure 1A) [19][20][21]. Phage crosses have been commonly used to exchange and combine phage genes involved in receptor recognition, resulting in altered host range, or to study the interaction between phages and newly identified bacterial defense systems [19,[21][22][23]. Phage crosses were also used for initial gene mapping strategies based on recombination frequencies, such as the mapping of the T4 rII loci responsible for the T4r phenotype of faster host degradation and bigger plaques [2].…”
Section: Homologous Recombinationmentioning
confidence: 99%
“…These cannot be random collections of bacteriophages, but rather need to include bacteriophages that use different attachment receptors and in which no reduced activity occurs through competition amongst the bacteriophages 22 . Once bacteriophages are identified that have desirable traits breeding and genetically modifying bacteriophages can also be used to enhance these desirable PJI treatment characteristics creating more effective therapeutics 23,24 . Overall, further research is needed to change the current PJI treatment paradigm, by creating specific PJI bacteriophage therapeutics and creating bacteriophage therapies that have an activity to CoNS and other common bacterial causes of PJI.…”
Section: Current Limitations Of Bacteriophagesmentioning
confidence: 99%